MEDIA LUAR RUANG DI KABUPATEN BENGKAYANG: ANALISIS VARIABEL FISIK, BAHASA, DAN HUKUM - Wulan, Cici Sri; Syahrani, Agus; Muzammil, Ahmad Rabi’ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research on the analysis physical, language, and legal variables on outdoor media in Bengkayang District. The object of this research is physical, language, and legal variables in outdoor media: (1) nameplate of government and private agencies; (2) nameplate of the place of trade: (3) outdoor advertising; (4) nameplate of housing and lodging; and (5) traffic and tourism instructions.The data were analyzed as many as 100 data processing objects which are the research domains, namely 20 nameplate data on government and private agencies, 20 nameplate data on the place of trading business, 20 data on outdoor advertising, 20 nameplate of housing and lodging, and 20 traffic and tourism instructions taken on several main roads in Bengkayang District.Based on the results of data analysis, there were 587 physical variable scores, 444 language variables, and 542 legal variables. After the final value of each number of variables was calculated, the total value of outdoor media in Bengkayang District, Bengkayang District showed results 497.5 which is included in the controlled criteria IV. Controlled criteria IV are areas where foreign language use is controlled by prioritizing Indonesian or regional languages.Keywords: Outdoor Media, Physical Variables, Language Variables, Legal Variables, Bengkayang District